2021
DOI: 10.1007/s13224-021-01559-x
|View full text |Cite
|
Sign up to set email alerts
|

Near-Miss Incidents in Obstetric Patients Admitted to an Intensive Care Unit of a Tertiary Care Center in Eastern India: A Retrospective Cohort Study

Abstract: Aim Obstetric patients presenting to the intensive care units (ICU) with or without underlying medical or surgical comorbidities can be a challenge to both the treating obstetrician and the intensivist. They occasionally present with near-miss events which if left untreated, can result in death. Objectives To study the prevalence, indications of ICU admissions, near-miss events, and their effect on mortality in obstetric and puerperal patients . … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(10 reference statements)
0
1
0
1
Order By: Relevance
“…En la investigación de 13 se menciona que en la Unidad de Cuidados Intensivos (UCI) el manejo de esta condición médica comprende la monitorización cardiaca por electrodos, pulsioximetría, presión arterial no invasiva, temperatura, diuresis, presiones venosas centrales y presiones arteriales invasivas. Una medida importante a tomar también es la gasometría arterial que debe realizarse dos veces al día y luego según lo requiriera la situación clínica.…”
Section: Resultsunclassified
“…En la investigación de 13 se menciona que en la Unidad de Cuidados Intensivos (UCI) el manejo de esta condición médica comprende la monitorización cardiaca por electrodos, pulsioximetría, presión arterial no invasiva, temperatura, diuresis, presiones venosas centrales y presiones arteriales invasivas. Una medida importante a tomar también es la gasometría arterial que debe realizarse dos veces al día y luego según lo requiriera la situación clínica.…”
Section: Resultsunclassified
“…Kumar et al study showed 7:1, whereas Roopa et al study showed 5.6:1. 15,19 If this maternal near miss indices shows positive deflection over period of time, it reflects on the improvement achieved in obstetric care.…”
Section: Discussionmentioning
confidence: 97%